Association to vegetated habitats and different vulnerability to habitat degradation for two fish species, Epinephelus areolatus (Serranidae) and Siganus canaliculatus (Siganidae), from the western Arabian Gulf. (April 2019) - Lin, Yu-Jia; Roa-Ureta, Ruben H.; Rabaoui, Lotfi; Grandcourt, Edwin Mark; Maneja, Rommel H.; Al-Abdulkader, Khaled; Qurban, Mohammad A.
Abstract: Epinephelus areolatus and Siganus canaliculatus are two species of fisheries importance associated with vegetated habitats, which are in turn threatened by human activities such as land filling. We tested their associations with vegetated habitats in the Arabian Gulf and examined essential life history traits to infer their vulnerability to the degradation of vegetated habitats. Epinephelus areolatus is found to be more abundant at deeper offshore vegetated habitats, while S. canaliculatus has higher abundance at shallow nearshore habitats. Epinephelus areolatus exhibits a longer life span, lower growth coefficient, larger size at 50% maturity, lower natural mortality, and protogynous sexual pattern, compared to Siganus canaliculatus . Accordingly, Epinephelus areolatus is expected to be more vulnerable to habitat degradation and environmental fluctuations. Different preferences in using vegetated habitats and degrees of vulnerability to habitat degradation for these two species could be further integrated to set priorities for management and conservation plans. Highlights: We examined the associations to vegetated habitats and the vulnerability to habitat degradation for these two species. The abundance of both Epinephelus areolatus and Siganus canaliculatus were associated with vegetated habitats. E. areolatus is predicted to be more vulnerable to habitat degradation based on life history traits. The sustainability of S. canaliculatus could be affected by the degradation of nearshore vegetated habitats.